Phaonia atrocyanea Ringdahl 1916 - Vikhrev, Nikita E.; Sorokina, Vera S. (Zenodo, 2017)
Phaonia atrocyanea Ringdahl, 1916 Material examined. RUSSIA: Altai Republic : 1♀, Seminskiy Pass, 51.05°N 85.59°E, 1650 m asl, 27– 30.06.2016, leg. N. Vikhrev (ZMUM). Distribution. Holarctic. Palaearctic: Norway, Sweden, Russia (Nenets AO, Taymyr Pen., Altai Mts). Nearctic: Canada (Yukon Territory, NWT, Labrador, Quebec), USA (Alaska). Published as part of Vikhrev, Nikita E. & Sorokina, Vera S., 2017, Taxonomic notes and faunistic data on the Muscidae (Diptera) of the Altai Mountains (Russia), pp. 241-254 in Zootaxa 4311 (2) on page 245, DOI:10.11646/zootaxa.4311.2.5, http://zenodo.org/record/847538